(untitled) (Universitas Scientiarum, 2014)
To develop proposals in bacterial formulations applicable to the agricultural sector, a study of physicochemical and biological parameters of the polymeric materials is essential. Here, we evaluated the effects of eight polymers on the cellular viability of Rhizobium sp. G58 during a 2-month period. From these results, we selected the three polymers that yielded the best results in respect to the survival of the bacteria. An assay of the effect of the polymers on the symbiotic activity of Rhizobium-Cowpea and the agronomic parameters was conducted under greenhouse conditions, based on the principal component analysis. A positive effect was found in Rhizobium sp. G58 using the Tukey’s Test (p<0.05) with sodium alginate (0.5-1%) and hydroxypropyl methylcellulose-HPMC (0.125-0.5%), while a significant decrease was established in cellular viability using polyethylene glycol-PEG, carbomer-Carbopol 940, and polyvinyl alcohol-PVA. The multivariate analysis indicated that the application of the polymers (sodium alginate and hydroxypropyl methylcellulose) in 0.5% concentration did not have negative effects on the symbiotic fixation of nitrogen or the process of nodulation. In conclusion, our results suggest the effectiveness of these polymers and the possibility of using them as carriers of bacterial formulation without affecting physiological processes.